Short 5'-flanking regions of the Amy gene of Drosophila kikkawai affect amylase gene expression and respond to food environments. - Inomata, N.; Nakashima, S. (Gene, 2008)
Evolution of the duplicated genes and regulation in gene expression is of great interest, especially in terms of adaptation. Molecular population genetic and evolutionary studies on the duplicated amylase genes of Drosophila species have suggested that their 5'-flanking (cis-regulatory) regions play an important role in evolution of these genes. For better understanding of evolution of the duplicated amylase genes and gene expression, we studied functional significance of the Amy1 gene of Drosophila kikkawai using in vitro deletion mutagenesis followed by P-element-mediated germline transformation. We found that a 1.6-kb of the 5'-flanking region can produce strikingly higher level of larval amylase activity on starch food compared with that on glucose food. We found two cis-regulatory elements, which increase larval amylase activity on starch food. We also found a larval cis-regulatory element, which responds to the food difference. This food-response element is necessary for the function of the element increasing larval activity on starch food. A 5-bp deletion in a putative GRE caused high amylase activity, indicating a cis-regulatory element decreasing amylase activity. These cis-regulatory elements identified in the 5'-flanking region could be the targets of natural selection.